Diffusion of light gases in 6FDA/BPDA-DAM Carbon Molecular Sieve membranes by Pulsed Field Gradient NMR - Mueller, Robert; Kanungo, Rohit; Kiyono-Shimobe, Mayumi; Koros, William J.; Vasenkov, Sergey (Diffusion Fundamentals, 2013)
In this paper, we demonstrate the potential of pulsed field gradient (PFG) NMR spectroscopy to reveal detailed knowledge of self-diffusion of light gases and light gas mixtures in carbon molecular sieve membranes on small length scales. PFG NMR is used to investigate intra-membrane diffusion of carbon dioxide and methane for a broad range of temperatures and mean square displacements in a carbon molecular sieve membrane derived from a 6FDA/BPDA-DAM polyimide film. Diffusion is investigated with single component sorbates as well as with a carbon dioxide / methane mixture. Results obtained from these studies are compared and discussed.